2011
DOI: 10.1002/jrs.2865
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Raman scattering in multilayer structures of porous silicon

Abstract: Multiple enhancement of the Raman scattering efficiency is observed in porous-silicon-based one-dimensional photonic bandgap (PBG) structures with tunable reflection and dispersion under excitation at 1.06 µm. The experimental results are explained as being due to the resonant increase in the effective Raman susceptibility at light wavelengths close to the PBG edges. This effect is discussed in view of possible applications in the Raman spectroscopy of molecules embedded in porous media as well as in the Raman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…[19] It can be also seen from Figure 2 that the intensity of Raman scattering exhibits a strong increase in the case of low doped SiNWs arrays, in comparison with c-Si wafers, which is related to the strong light scattering in SiNWs arrays. [9,20] The Raman intensity for the highly doped SiNWs is about two times lower than for the initial ones, which is caused both by the Fano effect [11] and absorption of the excitation light by free charge carriers. [21] The identical Raman peaks for low doped SiNWs and c-Si wafers (see Figure 2 and Table 1) indicate that SiNWs maintain the c-Si crystalline structure.…”
Section: Raman Spectra Of Highly Doped Silicon Nanowiresmentioning
confidence: 97%
“…[19] It can be also seen from Figure 2 that the intensity of Raman scattering exhibits a strong increase in the case of low doped SiNWs arrays, in comparison with c-Si wafers, which is related to the strong light scattering in SiNWs arrays. [9,20] The Raman intensity for the highly doped SiNWs is about two times lower than for the initial ones, which is caused both by the Fano effect [11] and absorption of the excitation light by free charge carriers. [21] The identical Raman peaks for low doped SiNWs and c-Si wafers (see Figure 2 and Table 1) indicate that SiNWs maintain the c-Si crystalline structure.…”
Section: Raman Spectra Of Highly Doped Silicon Nanowiresmentioning
confidence: 97%
“…Thus, the back reflected light might contribute to the enhancement of the local EM field around Ag NPs for pSi RFs and therefore also contribute to the overall SERS enhancement. Moreover, if the wavenumber of the Raman-scattered photons falls within the PBG of a periodic multilayered structure, a backward reflection of photons will result in their constructive interference, leading to further enhancement of Raman signals [68,69]. This principle was also expanded for SERS measurements [70] and, most recently, Zhong et al [71] reported an almost 4 fold increase in SERS EF by using pSi PhC.…”
Section: Resultsmentioning
confidence: 99%
“…Mamichev et al . reported enhanced Raman scattering from multilayer structures of PSi . Santangelo and co‐workers evaluated the degree of crystalline perfection of multi‐walled carbon nanotubes by means of correlations between thermal kinetic analysis and MRS …”
Section: Nanomaterialsmentioning
confidence: 99%